Diffusion controlled multilayer electrocatalysts via graphene oxide nanosheets of varying sizes. Issue 34 (17th August 2018) - Gu, Minsu; Choi, Jaewon; Lee, Taemin; Park, Minju; Shin, Ik-Soo; Hong, Jinkee; Lee, Hyun-Wook; Kim, Byeong-Su
Abstract : Controlling the architecture of hybrid nanomaterial electrodes is critical for understanding their fundamental electrochemical mechanisms and applying these materials in future energy conversion and storage systems. Abstract : Controlling the architecture of hybrid nanomaterial electrodes is critical for understanding their fundamental electrochemical mechanisms and applying these materials in future energy conversion and storage systems. Herein, we report highly tunable electrocatalytic multilayer electrodes, composed of palladium nanoparticles (Pd NPs) supported by graphene sheets of varying lateral sizes, employing a versatile layer-by-layer (LbL) assembly method. We demonstrate that the electrocatalytic activity is highly tunable through the control of the diffusion and electron pathways within the 3-dimensional multilayer electrodes. A larger-sized-graphene-supported electrode exhibited its maximum performance with a thinner film, due to facile charge transfer by the mass transfer limited in the early stage, while a smaller-sized-graphene-supported electrode exhibited its highest current density with higher mass loading in the thicker films by enabling facile mass transfer through increased diffusion pathways. These findings of the tortuous-path effect on the electrocatalytic electrode supported by varying sized graphene provide new insights and a novel design principle into electrode engineering that will be beneficial for the development of effective electrocatalysts.